Platelet‐derived growth factor‐AA is a substantial factor in the ability of adipose‐derived stem cells and endothelial progenitor cells to enhance wound healing. Issue 2 (28th September 2018) - Wu, Li-Wei; Chen, Wei-Liang; Huang, Shih-Ming; Chan, James Yi-Hsin
ABSTRACT: Nonhealing wounds with various forms of complications have been a major challenge for patients with different diseases, and few data are available regarding the clinical significance of platelet‐derived growth factor‐AA (PDGF‐AA) in the enhanced wound healing with stem cells, and the precise molecular mechanism remains unclear. The study aims to investigate the role of PDGF‐AA in adipose‐derived stem cells (ASCs) and endothelial progenitor cells (EPCs) enhancing wound healing. In this study, ASCs and EPCs were applied to treat wounds in an animal wound model with a wound‐healing assay. We knocked down PDGF‐AA expression in ASCs using the PDGF‐AA short hairpin RNA technique and investigated the related molecular mechanism. The wound model and wound‐healing assay of the study showed that transplantation of ASCs could enhance wound healing. The results showed that the PDGF‐AA knockdown ASC group had much less improvement of wound healing than other groups treated with wild‐type ASCs in wound tissues. The regulation of PDGF‐AA in ASCs may contribute to improve wound healing through the PI3K7Akt/eNOS signaling pathway. The data indicated that PDGF‐AA might play a vital role in ASCs and EPCs enhancing wound healing, possibly by its effects on angiogenesis. It would be a potential approach using PDGF‐AA for clinical treatment of chronic wounds.—Wu, L.‐W., Chen, W.‐L., Huang, S.‐M., Chan, J. Y.‐H. Platelet‐derived growth factor AA is a substantial factor in the ability of adipose‐derived stem cells and endothelial progenitor cells to enhance wound healing. FASEB J. 33, 2388–2395 (2019). www.fasebj.org